2016
DOI: 10.3390/met6080178
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Low Cycle Fatigue Behavior of Alloy 617 Base Metal and Weldments at 900 °C

Abstract: Abstract:In order to better understand the high temperature low cycle fatigue behavior of Alloy 617 weldments, this work focuses on the comparative study of the low cycle fatigue behavior of Alloy 617 base metal and weldments, made from automated gas tungsten arc welding with Alloy 617 filler wire. Low cycle fatigue tests were carried out by a series of fully reversed strain-controls (strain ratio, R ε =´1), i.e., 0.6%, 0.9%, 1.2% and 1.5% at a high temperature of 900˝C and a constant strain rate of 10´3/s. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…According to Wright et al [6], they confirmed that a decrease in peak flow stress followed by an increase in the strain range is characteristic of a solute drag creep deformation mechanism. Also, it has been reported in previous work that a consequence of the solute drag creep mechanism operating during LCF of Alloy 617 at high temperature ranges of 900-950 • C [6,7] was due to the amount of solute atoms motion, which reduces the flow stress.…”
Section: Monotonic and Low Cycle Fatigue Propertiesmentioning
confidence: 99%
See 3 more Smart Citations
“…According to Wright et al [6], they confirmed that a decrease in peak flow stress followed by an increase in the strain range is characteristic of a solute drag creep deformation mechanism. Also, it has been reported in previous work that a consequence of the solute drag creep mechanism operating during LCF of Alloy 617 at high temperature ranges of 900-950 • C [6,7] was due to the amount of solute atoms motion, which reduces the flow stress.…”
Section: Monotonic and Low Cycle Fatigue Propertiesmentioning
confidence: 99%
“…According to Wright et al [6], they confirmed that a decrease in peak flow stress followed by an increase in the strain range is characteristic of a solute drag creep deformation mechanism. Also, it has been reported in previous work that a consequence of the solute drag creep mechanism operating during LCF of Alloy 617 at high temperature ranges of 900-950 °C [6,7] was due to the amount of solute atoms motion, which reduces the flow stress. Branco et al [10] reported that evaluation of the variation of the cyclic softening with the total strain range during cyclic loading can be done through the characterization of the degree of softening (DOS), as given in Equation (3):…”
Section: Monotonic and Low Cycle Fatigue Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Several researchers have developed correlation models to predict the cyclic deformation behavior of steels from monotonic tensile properties and hardness [42][43][44][45]. Smith et al [46] discovered the correlation between the hardening or softening behavior and the ratio of ultimate tensile strength to yield strength (S u /S y ) from sixteen materials including steel, aluminium and titanium alloys.…”
Section: Correlation Among Monotonic Flow Curve and Cyclic Behavior Omentioning
confidence: 99%